BLUE LEISURE: INOVASI LITERASI EKOSISTEM LAUT DALAM PENDIDIKAN DASAR DI KABUPATEN BULELENG - Susila, Gede Hendri Ari; Budiadnyana, Anak Agung Ngurah (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Abstract: Buleleng Regency has a coastline of 157.05 kilometers with abundant marine ecosystem potential. However, this potential has not been optimally utilized in the education sector, particularly at the elementary school level. As a result, students’ marine ecosystem literacy remains low, along with limited involvement of the younger generation in coastal preservation and development efforts. The urgency of this study lies in the importance of integrating marine literacy into learning to foster environmental awareness from an early age. This research aims to analyze the need for marine tourism ecosystem literacy and develop contextual learning innovations through the Blue Leisure program as part of the Blue Sport Buleleng initiative. A descriptive quantitative and qualitative approach was employed through surveys and interviews with teachers and students in the western, central, and eastern regions of Buleleng. The findings indicate that 89.3% of respondents have never received marine education, yet 94% expressed interest in integrating marine literacy into the curriculum. These results confirm that Blue Leisure has strategic potential to promote marine literacy based on local resources and to foster an environmentally conscious younger generation.